Effect of the Duration of the Membership in GATT/WTO on Commercial Services Exports in Developing Countries - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2022)
The present article has investigated the effect of developing countries' duration of membership in the General Agreement on Tariffs and Trade (GATT) and the World Trade Organization (WTO) on their commercial services exports. It has relied on a set of 128 countries over the period from 2008 to 2019, and utilized the two-step system generalized method of moments estimator. It has revealed that the duration of membership in the GATT/WTO was associated with higher commercial services exports, including both modern and traditional services exports. However, Article XII Members (states that were not Members of GATT, but joined the WTO after its inception) have experienced higher commercial services exports (including traditional services exports) than Non-Article XII Members (i.e., states that were GATT Members before the creation of the WTO). For low-income member states, the membership duration has resulted in an increase in traditional services exports at the expense of modern services exports. Conversely, relatively wealthier member states have increased modern services exports at the expense of traditional services exports, as their membership duration rose. The analysis has also established that member states that have improved their capacities to use, adopt and adapt frontier technologies have enjoyed higher commercial services exports, including modern services exports, but have not experienced an increase in traditional services exports. Finally, the duration of membership in the GATT/WTO has led to higher commercial services exports, including both modern and traditional services exports for member states that have improved their penetration in the international markets for goods. The policy implications of the analysis are discussed.
Keywords: F15; O14; F53; 330; Duration of membership in the GATT/WTO; Commercial services exports; Frontier technology readiness; Penetration in goods markets